(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
People with intellectual disabilities often have to cope with movement and body awareness disorders. Special educators’ assess movement and body awareness in order to determine the level and quality of movement performance, body conception, as well as the lateralization of movement and body. Movement and dance therapy are new rehabilitation methods and treatment to aid with these disorders. This article discusses the differences between the concepts of movement, body schema, body image, and body awareness in order to highlight the importance of these concepts in the physical and mental development of the child, and adulthood. The article pays special attention to the impact of the Covid 19 pandemic on movement and body awareness therapy and rehabilitation methods.